Canva-based Animation Comic Video Media in Informatics Learning at SMP Negeri 14 Padang - Huda, Asrul; Sari, Liza Mustika; Effendi, Hansi; Giatman, Muhammad; Sukmawati, Murni; Firdaus, - (JOIV : International Journal on Informatics Visualization, 2025)
This research addresses challenges in conventional learning media, limited facilities, and suboptimal use of technology, which hinder student material mastery, motivation, and independence. The study aims to develop and validate Canva-based animated comic video learning media for Informatics subjects in class VIII at SMP N 14 Padang. Using the Research and Development (R&D) method with a 4D development model—define, design, develop, disseminate—primary data were collected from validators, teachers, and students. Descriptive and inferential analyses were employed to evaluate the validity and practicality of the media. The learning media achieved high validity scores: 0.963 for media design and 0.975 for material content. Expert evaluations highlighted the media’s effective visual design, systematic content presentation, and alignment with curriculum objectives. Practicality was confirmed with average scores of 97.04% from teachers and 93.14% from students, who appreciated its ease of use, accessibility across devices, and engaging, interactive features that support both independent and collaborative learning. This study underscores the importance of integrating technology into learning media to enhance education quality. Canva-based animated comic videos are not only applicable to Informatics but also have potential for adaptation to other subjects. The combination of visual, audio, and interactive elements fosters engaging, flexible, and impactful learning experiences for students. Future research could explore AI integration for personalized learning and broader testing across diverse student groups and subjects. This research provides a foundation for developing innovative, accessible, and inclusive technology-based learning tools to improve education quality in the digital era.